CALIBRATION PROCEDURE FOR THE “SMARTCHANNEL” DEVICE (Irrigation and Melioration, 2026)
This article presents a methodology for evaluating and calibrating the metrological characteristicsof the “Smart Channel” device designed for measuring water discharge in open channels under laboratory conditions. An 80×80 cm device sample was selected as the research object. Theexperiments were conducted in the “Hydraulics and Hydrometry” laboratory of “Smart SolutionsSystem” LLC, located in the Kuyichirchik district of Tashkent region. The device operates basedon the velocity–area method, in which water discharge is determined using the average flowvelocity and wetted cross-sectional area. Flow velocity is recorded layer by layer using a totalof 32 ultrasonic sensors arranged in 8 rows, and the overall average velocity is then calculated.During the study, the maximum water conveyance capacity of the device and its errors comparedwith an electromagnetic reference flowmeter and the volumetric method were determined. In theinitial tests, the maximum discharge was 799.23 l/s, while the errors ranged from 5.98% to 14.30%.This indicated the need to improve the initial calculation algorithm of the device under high-flowconditions. Therefore, a calibration coefficient was developed based on the results obtained from thereference flowmeter and the volumetric method and was integrated into the device software. Aftercalibration, the maximum discharge increased to 890.57 l/s, while the errors decreased to the rangefrom 2.47% to +2.37%. The results showed that verification and calibration significantly improvedthe accuracy of the device, provided a scientific and practical basis for reliable digital measurement of water discharge in open channels, and supported the effective implementation of the device in practice.